Penyusunan Laporan Keuangan Dan Pengembangan Usaha Jasa Pada UMKM Loundry Mommy - Allisha Triana Purie; Cindy Indrawati; Hadi Lidya Rikayana (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
Laundry services are one of the service businesses that have good prospects today. Because city people are getting busier, making laundry service businesses increasingly in demand and competition for similar service provider companies is getting tighter so that companies must improve service quality so that consumers continue to subscribe to using these laundry services. However, we find that many MSME players still have not or do not record financial reports so that these MSME players have difficulty knowing the details of their business activities so far, whether they are making a profit or even experiencing a loss. Therefore, the researcher here helps the owner to record financial reports so that in the future the owner can find out the profit and how to make this laundry service business grow. The research method used in this case uses the Descriptive method, where researchers go directly to the field to conduct observations and interviews with the owner of Mommy's laundry. In this study, researchers have assisted laundry service business owners in recording financial reports that occur, so that in the future it is hoped that laundry owners can make their own records for the development and sustainability of the business.